2006
DOI: 10.4049/jimmunol.177.8.5393
|View full text |Cite
|
Sign up to set email alerts
|

V(D)J Recombinase-Mediated Processing of Coding Junctions at Cryptic Recombination Signal Sequences in Peripheral T Cells during Human Development

Abstract: V(D)J recombinase mediates rearrangements at immune loci and cryptic recombination signal sequences (cRSS), resulting in a variety of genomic rearrangements in normal lymphocytes and leukemic cells from children and adults. The frequency at which these rearrangements occur and their potential pathologic consequences are developmentally dependent. To gain insight into V(D)J recombinase-mediated events during human development, we investigated 265 coding junctions associated with cRSS sites at the hypoxanthine-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 54 publications
1
26
1
Order By: Relevance
“…Cryptic recombination signal sequences are distributed every 40 -50 bp throughout the genome, including both immune and nonimmune loci (39), and it is becoming increasingly clear that rag-mediated rearrangements at these cryptic sites can occur in the absence of gross translocations. Nonpathogenic rearrangements have been most extensively studied at the HPRT locus in which rag activity is associated with three different deletions in T cells from healthy newborns and young adults (40,41). V(D)J rearrangements at cryptic recombination signal sequences are also detectable in ␥-satellite DNA, a highly repetitive DNA element encompassing ϳ6% of the mouse genome (42).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptic recombination signal sequences are distributed every 40 -50 bp throughout the genome, including both immune and nonimmune loci (39), and it is becoming increasingly clear that rag-mediated rearrangements at these cryptic sites can occur in the absence of gross translocations. Nonpathogenic rearrangements have been most extensively studied at the HPRT locus in which rag activity is associated with three different deletions in T cells from healthy newborns and young adults (40,41). V(D)J rearrangements at cryptic recombination signal sequences are also detectable in ␥-satellite DNA, a highly repetitive DNA element encompassing ϳ6% of the mouse genome (42).…”
Section: Discussionmentioning
confidence: 99%
“…We used these samples to compare coding joint processing at selected TCRb locus RSS with that previously observed in the same populations at a nonimmune cRSS at the HPRT locus (14). Mutant HPRT T cell clones were isolated using the HPRT T cell-cloning assay that selects for individual T cells that have acquired an in vivo mutation resulting in a loss of HPRT activity, as previously described (17,18).…”
Section: V(d)j Recombinase-mediated Tcrb Gene Usage and Coding Joint mentioning
confidence: 99%
“…V(D)J recombinase can also mediate rearrangements at nonimmune or "cryptic" RSS in normal and leukemic human peripheral T cells. We previously demonstrated age-and gender-specific developmental differences in V(D)J coding joint processing at cryptic RSS within the HPRT locus in peripheral T cells from healthy children (Murray et al 2006. J. Immunol.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Studies by Murray et al have demonstrated genderspecific V(D)J recombinase-mediated TCRb gene usage and coding joint processing in human development that demonstrate direct effects on TCR diversity, though these studies were conducted on healthy children at a maximum age of 12.5 y. 63,64 In this study, these gender-specific differences in clonality did not occur across compartments -an observation that did occur with age-related associations, thus the strength of this gender-specific observation in NSCLC needs to be further evaluated in subsequent studies.…”
Section: E1051922-6 Volume 4 Issue 12 Oncoimmunologymentioning
confidence: 99%